2017
DOI: 10.1016/j.spinee.2017.08.167
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Robot-Assisted Pedicle Screw Insertion in Adolescent Idiopathic Scoliosis: Is Triggered Electromyographic Pedicle Screw Stimulation Necessary?

Abstract: Background: Screw malpositioning is an identifiable cause of intraoperative neurophysiologic changes.Although triggered screw electromyography (t-EMG) has been found to exhibit high sensitivity for identifying malpositioned screws, no previous study has assessed the utility of combining t-EMG with robotic-assisted pedicle screw placement for identifying malpositioned screws. We sought to evaluate the utility of t-EMG used in combination with robotic-assisted pedicle screw placement for identifying malpositione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…9,19 As all studies concluded, the robot assisted pedicle screw placement is a safe and effective technique and is also cost-effective. [20][21][22] In our cohort, the robot-assisted spine surgery was scheduled in 62 cases; however, only in 46 patients (74.2%) was it used due to system setup failure. This was caused due to registration in 1 patient, installation process in 13 cases, software bug in 1 case or placement in another patient.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 As all studies concluded, the robot assisted pedicle screw placement is a safe and effective technique and is also cost-effective. [20][21][22] In our cohort, the robot-assisted spine surgery was scheduled in 62 cases; however, only in 46 patients (74.2%) was it used due to system setup failure. This was caused due to registration in 1 patient, installation process in 13 cases, software bug in 1 case or placement in another patient.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the misplacement of pedicle screws in AIS, extra-pedicle screws [20], PPSs, cannulate pedicle screws [8], intraoperative navigation, robot-assisted pedicle screws [21] and 3D-printing drill guide template [22] have been developed. Recently, some studies have reported the clinical use of cannulated pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient was classified as having a threshold ≤8 mA was defined as abnormal and underwent screw re-direction, but underwent screw removal and probing of the pedicle track using a ball-tip probe. This information has been clarified in the text for better understanding [20].…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…Pedicle screw misplaced rates using conventional techniques ranged from 5 to 41% in the lumbar spine and from 3 to 55% in the thoracic spine [18,19], with an estimated 1% rate of neurologic complication. Triggered screw electromyography (t-EMG) has been used to help identify misplaced screws, with threshold stimulation varying based upon the spinal segment tested (lumbar versus thoracic), location within the curve (apical versus non-apical) and laterality with regard to the curve (concavity versus convexity) [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation